Bit‐level implementation for polynomial cancellation coded DFT‐s‐OFDM transmitters. Issue 5 (1st March 2020) - Cho, L.; Hsu, C.‐Y.
Abstract : Polynomial cancellation coded discrete Fourier transform‐spread orthogonal frequency division multiplexing (PCC‐DFT‐s‐OFDM) is famous for the flexibility of DFT‐s‐OFDM on the trade‐off between peak‐to‐average power ratio performance and spectral efficiency. Deploying it on numerous user equipments (UEs) as enhanced uplink signalling becomes a practical issue. In this Letter, a bit‐level implementation of PCC mapping is proposed, so that the compatibility of implementation of corresponding circuits on UE transmitters would make the deployment more easily. By taking Long Term Evolution and New Radio standards as examples, the equivalency of bit/symbol‐level implementations is validated in terms of bit error rate performance.